Efecto mionecrótico del veneno de Aphonopelma seemanni (Araneae: Theraphosidae) de Costa Rica en ratón blanco - Herrero, Marco V.; Gutiérrez, José María (Revista de Biología Tropical, 1984)
The venom of female spiders (Aphonopelma seemanni) induces necrosis of skeletal muscle in mice. This effect was demonstrated by histology and by the increase in the plasma levels of the enzyme creatine kinase (CK).